Correlative analysis of structure and chemistry of LixFePO4 platelets using 4D-STEM and X-ray ptychography. (January 2022) - Hughes, L.A.; Savitzky, Benjamin H.; Deng, Haitao D.; Jin, Norman L.; Lomeli, Eder G.; Yu, Young-Sang; Shapiro, David A.; Herring, Patrick; Anapolsky, Abraham; Chueh, William C.; Ophus, Colin; Minor, Andrew M.
Graphical abstract: Abstract: Lithium iron phosphate (Lix FePO4 ), a cathode material used in rechargeable Li-ion batteries, phase separates upon de/lithiation under equilibrium. The interfacial structure and chemistry within these cathode materials affects Li-ion transport, and therefore battery performance. Correlative imaging of Lix FePO4 was performed using four-dimensional scanning transmission electron microscopy (4D-STEM), scanning transmission X-ray microscopy (STXM), and X-ray ptychography in order to analyze the local structure and chemistry of the same particle set. Over 50, 000 diffraction patterns from 10 particles provided measurements of both structure and chemistry at a nanoscale spatial resolution (16.6–49.5 nm) over wide (several micron) fields-of-view with statistical robustness. Lix FePO4 particles at varying stages of delithiation were measured to examine the evolution of structure and chemistry as a function of delithiation. In lithiated and delithiated particles, local variations were observed in the degree of lithiation even while local lattice structures remained comparatively constant, and calculation of linear coefficients of chemical expansion suggest pinning of the lattice structures in these populations. Partially delithiated particles displayed broadly core–shell-like structures, however, with highly variable behavior both locally and per individual particle that exhibited distinctive intermediate regions at the interface between phases, and pockets within the lithiated core that correspond to FePO4 in structure and chemistry. The results provide insight into the Lix FePO4 system, subtleties in the scope and applicability of Vegard's law (linear lattice parameter-composition behavior) under local versus global measurements, and demonstrate a powerful new combination of experimental and analytical modalities for bridging the crucial gap between local and statistical characterization.